2021
DOI: 10.1371/journal.ppat.1009773
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1: A new diagnostic biomarker for human tuberculosis discovered using Diversity Outbred mice

Abstract: More humans have died of tuberculosis (TB) than any other infectious disease and millions still die each year. Experts advocate for blood-based, serum protein biomarkers to help diagnose TB, which afflicts millions of people in high-burden countries. However, the protein biomarker pipeline is small. Here, we used the Diversity Outbred (DO) mouse population to address this gap, identifying five protein biomarker candidates. One protein biomarker, serum CXCL1, met the World Health Organization’s Targeted Product… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 43 publications
(104 reference statements)
3
62
0
Order By: Relevance
“…Lung CFU was strongly correlated with weight loss, mediators that enhance neutrophil differentiation or migration (CXCL2 (MIP-2; r = 0.79), CCL3 (MIP-1a; r = 0.77), G-CSF ( r = 0.78), and CXCL1 (KC; r = 0.76)), and more general proinflammatory cytokines (IL-6 ( r = 0.80) and IL-1α ( r = 0.76)) ( Figure 1—figure supplement 1 ). These findings are consistent with previous work in the DO panel, that found both proinflammatory chemokines and neutrophil accumulation to be predictors of disease ( Ahmed et al, 2020 ; Gopal et al, 2013 ; Koyuncu et al, 2021 ; Niazi et al, 2015 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Lung CFU was strongly correlated with weight loss, mediators that enhance neutrophil differentiation or migration (CXCL2 (MIP-2; r = 0.79), CCL3 (MIP-1a; r = 0.77), G-CSF ( r = 0.78), and CXCL1 (KC; r = 0.76)), and more general proinflammatory cytokines (IL-6 ( r = 0.80) and IL-1α ( r = 0.76)) ( Figure 1—figure supplement 1 ). These findings are consistent with previous work in the DO panel, that found both proinflammatory chemokines and neutrophil accumulation to be predictors of disease ( Ahmed et al, 2020 ; Gopal et al, 2013 ; Koyuncu et al, 2021 ; Niazi et al, 2015 ).…”
Section: Resultssupporting
confidence: 92%
“…Together, these resources have been leveraged to identify host loci underlying the immune response to infectious diseases ( Noll et al, 2019 ). In the context of TB, DO mice have been used as individual, unique hosts to identify correlates of disease, which resemble those observed in non-human primates and humans ( Ahmed et al, 2020 ; Gopal et al, 2013 ; Koyuncu et al, 2021 ; Niazi et al, 2015 ). Small panels of the reproducible CC strains have been leveraged to identify host background as a determinant of the protective efficacy of BCG vaccination ( Smith et al, 2016 ) and a specific variant underlying protective immunity to tuberculosis ( Smith et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, this work demonstrates that while the biomarkers CXCL1, MMP8, IL-10, IFN-γ, and TNF-α can be detected in Asian elephant serum, they are unlikely to share the same utility in elephant TB that they possess in human TB given that they are not elevated in clinically healthy M.tb culture-positive elephants. This finding may differ with disease state, as experimental studies 17 using human sera have shown significantly higher concentrations of CXCL1 and MMP8 in patients with active pulmonary TB (ie, exhibiting clinical signs) compared to latent M.tb infection (ie, not clinically ill). Given their lack of clinical signs, M.tb culture-positive elephants in this study were likely asymptomatically infected, analogous to humans with latent M.tb infection.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarkers chemokine (C-X-C motif) ligand 1 (CXCL1), matrix metalloproteinase 8 (MMP8), interleukin-10 (IL-10), interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α) have been shown to be significantly elevated in the serum of Diversity Outbred mice infected with M.tb compared to noninfected mice, and this research recently showed translational relevance to humans. 17 In this study, we sought to determine (1) if these 5 biomarkers could be detected in serum from Asian elephants, and (2) if the serum concentrations of these 5 biomarkers are significantly elevated in M.tb culture-positive elephants compared to M.tb culture-negative elephants. We predicted that these biomarkers would be both detectable and significantly elevated in serum from M.tb culture-positive elephants compared to M.tb culture-negative elephants.…”
mentioning
confidence: 99%
“…By applying machine learning algorithms to multidimensional data, the authors discovered CXCL1 as a putative biomarker of TB in the serum of mice. The biomarker was further validated in samples derived from human patients, discriminating active TB from latent infection and non-TB lung disease [ 45 ]. This study highlights the relevance of using population-based strategies to accelerate human biomarker discovery, validation, and testing.…”
Section: Rodents As Model Organisms In Genetic Research: Advantages A...mentioning
confidence: 99%